2017
DOI: 10.3390/su9101918
|View full text |Cite
|
Sign up to set email alerts
|

R&D Project Selection Incorporating Customer-Perceived Value and Technology Potential: The Case of the Automobile Industry

Abstract: Abstract:As user-centric innovation has recently emerged as a successful way of developing new products, services, and concepts, it is worth considering the perspectives of potential technology users during R&D project selection processes. Nevertheless, little effort has been made to reflect customer-perceived value in establishing selection criteria, with the focus mainly on technological potential instead. Therefore, this study aims to develop an R&D project selection model incorporating not only technologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Chebat and Michon (2003) found that environmental cues of ambiance directly affected shoppers' perceptions and that customers' pleasure was increased by more positive ambient conditions. Similarly, Cho and Lee (2017) recognized a optimistic relationship between environmental prompts such as ambient condition and the level of customers' pleasure and purchase intention. Further literature also supports that ambiance evokes consumers' positive behavioral responses.…”
Section: Elements Of Retailscapementioning
confidence: 99%
“…Chebat and Michon (2003) found that environmental cues of ambiance directly affected shoppers' perceptions and that customers' pleasure was increased by more positive ambient conditions. Similarly, Cho and Lee (2017) recognized a optimistic relationship between environmental prompts such as ambient condition and the level of customers' pleasure and purchase intention. Further literature also supports that ambiance evokes consumers' positive behavioral responses.…”
Section: Elements Of Retailscapementioning
confidence: 99%
“…Nevertheless, little effort has been made to reflect customer-perceived value in establishing criteria to select innovation projects. This applies also, as [17] stated, to the reflection of their interest in innovative, environmentally friendly product features. In the CE context, specific preferences and the role of the end-users of more sustainable cars such as electric vehicles (EVs) and biofuels are unknown so far.…”
Section: Ce Innovation Ecosystems and User Integration In The Automotmentioning
confidence: 87%
“…Ref. [17] emphasized the importance of considering customer-perceived values in establishing selection criteria in innovation management decisions. Likewise, they stressed that the automotive industry is substantially a business-to-consumer sector, in which incorporating customer requirements is critical to innovation.…”
Section: Ce Innovation Ecosystems and User Integration In The Automotmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing studies are mostly related to the project selection itself or approached by introducing new methodologies to select the projects, not considering market-related factors. Lee et al [20] addressed R&D project selection with customer-perceived value and technological potential. However, the study was not extended to consider market-related factors such as sales.…”
Section: Introductionmentioning
confidence: 99%